Development of Higher Order Thinking Skills Assessment Refer the Theory of Bloom in Laboratory Work - Soka Hadiati; Eti Sukadi; Adi Pramuda (AL-ISHLAH: Jurnal Pendidikan, 2021)
Higher-order thinking skills (HOTS) are one of the important components that students must master to be successful in the 21st century. The HOTS of students in several regions in Indonesia is low because HOTS-based learning and the instruments are not appropriate. This study aims to determine the validity and reliability of the HOTS assessment content, empirical, and constructs referring to bloom theory in laboratory work. The development model used is the Plomp development model, which consists of five stages: initial investigation, design, realization/construction, test, evaluation and revision, and implementation. The HOTS assessment was proven relevant by experts and then distributed to 70 Physics Education students. The HOTS assessment was analyzed by rash model theory analysis with the Winstep program to obtain empirical validity. SEM (Structural Equation Model) was used to obtain construct validity. The results showed that the HOTS assessment was valid and reliable. The results show that the assessment has been able to measure every aspect of HOTS well in laboratory work so that it can be used.